2020
DOI: 10.1186/s12974-020-1712-0
|View full text |Cite
|
Sign up to set email alerts
|

Paroxetine suppresses reactive microglia-mediated but not lipopolysaccharide-induced inflammatory responses in primary astrocytes

Abstract: Background: Astrocytes are the most abundant glial cells in a brain that mediate inflammatory responses and provide trophic support for neurons. We have previously disclosed that paroxetine, a common selective serotonin reuptake inhibitor, ameliorates LPS-induced microglia activation. However, it remains elusive for the role of paroxetine in astrocytic responses. Methods: Isolated primary astrocytes were pretreated with paroxetine and stimulated with different stimuli, lipopolysaccharide (LPS) or microglia con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…First, we focused on comparing the effects of the three Kampo formulas on aging-related emotional disturbances and neuroinflammation in SAMP8 mice and found that they exerted preventive effects against depression-like behaviors as well as neuroinflammation associated with aging. Some antidepressants have been reported to attenuate neuroinflammation in vivo [ 24 , 85 ] and in vitro [ 86 89 ], as well as in human studies [ 25 ]. Further studies comparing the effects of these Kampo formulas with those of existing antidepressants are necessary for proper evaluation of the efficacy of Kampo medication as a treatment for late-life depression.…”
Section: Discussionmentioning
confidence: 99%
“…First, we focused on comparing the effects of the three Kampo formulas on aging-related emotional disturbances and neuroinflammation in SAMP8 mice and found that they exerted preventive effects against depression-like behaviors as well as neuroinflammation associated with aging. Some antidepressants have been reported to attenuate neuroinflammation in vivo [ 24 , 85 ] and in vitro [ 86 89 ], as well as in human studies [ 25 ]. Further studies comparing the effects of these Kampo formulas with those of existing antidepressants are necessary for proper evaluation of the efficacy of Kampo medication as a treatment for late-life depression.…”
Section: Discussionmentioning
confidence: 99%
“…As a comparison, in a recent study where primary astrocytes were cultured with serum-containing medium, paroxetine was shown to suppress microglia-conditioned medium-stimulated astrocytic inflammation partially via the p65/NFκB pathway, but not by STAT3 and JNK1/2. In addition, paroxetine showed no impact on lipopolysaccharide-induced astrocytic responses [ 21 ]. These results indicate that the phenotype (A1, A2, resting, or mixed) and the stimulus matter how antidepressants play a role in astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…As previously described [ 21 ], cells were fixed in 4% paraformaldehyde for 30 min and washed with phosphate-buffered saline (PBS), followed by permeabilization in 0.2% Triton X-100 for 20 min. Samples were blocked with 5% bovine serum albumin (ST023; Beyotime, Shanghai, China) for 1 h and then incubated with primary antibodies against GFAP (MAB360; Merck Millipore, Billerica, MA, USA), p65 (8242; Cell Signaling, Boston, MA, USA), C3 (EPR9394; Abcam, Cambridge, UK), or S100A10 (11250-1-AP; Proteintech, Rosemont, IL, USA) at 4 °C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is widely utilized in neuroscience research to generate in vitro inflammation models. Accumulating evidence has shown that LPS can trigger astrocytes to release pro-inflammatory cytokines, which damage to the surrounding neurons ( Sun et al, 2016 ; Zhang et al, 2020 ). Consistently, we observed significant increases in the expression of inflammatory factors, including IL-1β, IL-6, IL-10, and TNF-α, in reactive astrocytes following stimulation with LPS.…”
Section: Discussionmentioning
confidence: 99%
“…Lipopolysaccharide (LPS) and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) are widely used to produce animal models of PD ( Jackson-Lewis and Przedborski, 2007 ; Meredith et al, 2008 ). LPS, an endotoxin is often used for both in vivo and in vitro PD model to study the mechanism of the neuroinflammation, and its toxic effect is due to the dopaminergic vulnerability to the substantia nigra ( Herrera et al, 2000 ; Gao et al, 2011 ; Wang et al, 2016 ; Zhang et al, 2020 ). As for MPTP, 1-methyl-4-phenylpyridinium (MPP + ) is the ultimate mediator of the neurotoxicity of MPTP.…”
Section: Introductionmentioning
confidence: 99%